2018
DOI: 10.3390/met8020122
|View full text |Cite
|
Sign up to set email alerts
|

Strain Hardening Behavior and Microstructure Evolution of High-Manganese Steel Subjected to Interrupted Tensile Tests

Abstract: Strain hardening behavior and the corresponding microstructure evolution of the high-manganese steel with additions of Si and Al were investigated in this study. Thermomechanically processed and solution-heat-treated sheet steels were compared under conditions of interrupted tensile tests. Relationships between microstructure and strain hardening were assessed for different strain levels using light microscopy and scanning electron microscopy techniques. It was found that the deformation of both steels at low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…From a technological point of view, the PLC and DSA effects must be avoided. The DSA phenomenon gives rise to non-homogeneous plastic flow during the sheet-forming processes and may lead to surface defects on formed parts [17][18][19]. Our previous reports on thermomechanically processed medium-Mn sheet steels indicate that the problem can be avoided [7].Newly developed fine-grained ferrite-austenite or bainitie-austenite steels contain manganese in a range of 3-12%, while carbon content is ca.…”
mentioning
confidence: 99%
“…From a technological point of view, the PLC and DSA effects must be avoided. The DSA phenomenon gives rise to non-homogeneous plastic flow during the sheet-forming processes and may lead to surface defects on formed parts [17][18][19]. Our previous reports on thermomechanically processed medium-Mn sheet steels indicate that the problem can be avoided [7].Newly developed fine-grained ferrite-austenite or bainitie-austenite steels contain manganese in a range of 3-12%, while carbon content is ca.…”
mentioning
confidence: 99%
“…An Epsilon high temperature extensometer was used in the tensile test to measure the uniform deformation of the specimen, but the stress-strain curve of the material after necking is no longer reliable and is thus calculated by an FE-based inverse modeling procedure in this research. Many researchers [2,4,20] have proposed several FE-based inverse methods respectively and we used a modified inverse method based on the early work of Joun [20].…”
Section: Fe-based Inverse Modeling Proceduresmentioning
confidence: 99%
“…The simulation of metal forming process is a highly non-linear problem involving large material deformation and complex boundary conditions [2] which requires accurate hardening behavior of the investigated sheet metal over a wide range of plastic strains. Till now the most popular method to obtain the stress-strain relationship of metal sheet, represented either in the form of a set of discrete data points or analytical constitutive models, is typically by conducting standard uniaxial tensile test with rectangular cross-section [3,4]. The stress and strain values of the uniaxial tensile test can be obtained by using an extensometer that measures the elongation of a certain gauge length but the calculated stress value is accurate on the assumption that the test specimen is subjected to homogeneous state of uniaxial loading, which means that the stress-strain relationship identified by standard uniaxial tensile test is valid only before the so-called diffuse necking large strains under uniform deformation.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, one should note that the rapid degradation represented by a necking-failure phenomena occurred immediately after reaching the tensile strength. Earlier studies reported that microstructural effects such as martensite formation and mechanical twinning contributed to the strengthening of high manganese steel and delayed the onset of necking, which is associated with large uniform elongation [24][25][26][27][28][29]. Based on these features, strength-based design is typically performed for industrial structures and can lead to structural safety problems with respect to excessive deformation and rapid necking-fracture in high manganese steel.…”
Section: Introductionmentioning
confidence: 99%
“…Step 4: the modified calculation of (·) n+1 considering the plastic region through return mapping is carried out as shown in Equations (19)(20)(21)(22)(23)(24).…”
mentioning
confidence: 99%